Business-local government Interdependence and Corporate Social Responsibility Intention in China - LYU, Weixing; XIE, Xuanli; HAN, Yi (Advances in Social Sciences Research Journal, 2018)
This research examines how business-local government interdependence influences firm corporate social responsibility (CSR) intention. Specifically, based on resource dependence theory, we propose that when firms are more dependent on political resources possessed by local government, firms would be more intent to use CSR as a political instrument to restructure their interdependence with local government; when local government is more dependent on firm economic resources, firms may shirk CSR opportunistically. Moreover, we suggest that the above relationship be contingent on firm pollution visibility, political connections, and the claim urgency of the local government. We use a nation-wide survey of 1,268 firms to test these hypotheses and obtain supports from the statistical analysis.